ANALISIS KESIAPAN GURU MI/SD DALAM MENGHADAPI KURIKULUM MERDEKA - Quraniyah, Risa Lailatul; Herianingtyas, Nur Luthfi Rizqa (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
The purpose of this research is to find out how prepared MI/SD teachers are in facing the Independent Curriculum. This study used a questionnaire distributed via Google Form to collect quantitative and descriptive data. The consequence of this research is that educators need to know various things before integrating self-education plans into learning exercises, for example there are three types of learning exercises in the Free Education program: Learning outside the classroom; Pancasila Student Profile Project; extracurricular learning. The educational program structure for determining study hours is written all at once for one year. The idea of the percentage of study hours per follow-up is based on a standard or week-by-week premise. Independent Curriculum Core Competencies (KI) must then be transformed into Teaching Modules, Learning Outcomes (CP), and Learning Objectives Flow (ATP). To ensure that education programs can be implemented successfully and provide significant growth opportunities in stages, it requires the commitment of school foundations to provide adequate support and capital to educators